2011
DOI: 10.1590/s1516-35982011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e valor nutricional da silagem de híbridos de milho em diferentes alturas de colheita

Abstract: RESUMO -Cinco híbridos de milho foram avaliados quanto à produtividade de matéria seca, ao valor nutritivo da silagem e à produtividade de leite. Os híbridos avaliados foram AS 32, AG 9090, CD 308, DKB 747 e P 30F87, colhidos em três alturas de corte: 15, 35 e 55 cm. O delineamento experimental foi em blocos casualizados com parcelas subdivididas e três repetições.Para confecção das silagens, utilizaram-se silos experimentais de PVC com 20 cm de diâmetro e 40 cm de altura. A produtividade de leite, por tonelad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
0
12
1
9
Order By: Relevance
“…For each 0.10 m increase, there was a decrease of 22.2, 128.0, 297.3, 140.2, 157.0, 119.5, 37.6 and 29.3 kg ha -1 , respectively. This contrasts with reports by Oliveira et al (2011), who did not observe differences in EE and CP production with the increase in cutting height from 0.15 m to 0.55 m, and Vasconcelos et al (2005), who also did not find differences in CP yields (kg ha -1 ) in the ensilable phytomass. However, both described a reduction of 24% in NDF and 29% in the FAD, with an increase in the cutting height from 0.10 m to 0.80 m. Nutrient depletion from the soil through biomass harvesting also displayed a linear decrease with increasing cutting heights (Table 4).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…For each 0.10 m increase, there was a decrease of 22.2, 128.0, 297.3, 140.2, 157.0, 119.5, 37.6 and 29.3 kg ha -1 , respectively. This contrasts with reports by Oliveira et al (2011), who did not observe differences in EE and CP production with the increase in cutting height from 0.15 m to 0.55 m, and Vasconcelos et al (2005), who also did not find differences in CP yields (kg ha -1 ) in the ensilable phytomass. However, both described a reduction of 24% in NDF and 29% in the FAD, with an increase in the cutting height from 0.10 m to 0.80 m. Nutrient depletion from the soil through biomass harvesting also displayed a linear decrease with increasing cutting heights (Table 4).…”
Section: Resultscontrasting
confidence: 99%
“…Consequently, cutting height had a positive linear effect on the TDN and RFV indexes (Table 6), with a cutting height increase from 0.20 to 1.00 m corresponding to a 16.4% rise in silage TDN (from 65.9 to 76.7%), whereas RFV increased by 13% for each 0.10 m cutting height increase. Oliveira et al (2011) observed a less marked increase in the TDN value (6.7%) after an increase in the cutting height from 0.15 m to 0.55 m. Conversely, MM, Ca and Mg decreased linearly with cutting height (Table 6). …”
Section: Resultsmentioning
confidence: 86%
“…Mesmo comportamento foi observado em outros trabalhos (1,2,15,25) , uma vez que cortes mais baixos apresentam maiores contribuição de colmo na massa ensilada. Assis et al (26) , avaliando as características de híbridos para ensilagem, observaram que os materiais que apresentaram maiores teores de lignina também apresentaram maiores proporções de colmo.…”
Section: Resultsunclassified
“…No entanto, com a elevação da altura de corte ocorre redução na massa de forragem ensilável (2) . Assim, a tomada de decisão deve considerar a relação custo:benefício (quantidade vs. qualidade) do volumoso produzido.…”
Section: Introductionunclassified
“…-valdez et al (2013) observed greater DM, NDF, ADF and pH when bromatological composition of sugarcane silage was compared to fresh material with no differences for protein nor rumen pH, and lower in situ DM digestibility. Roman et al (2011) worked with sugarcane silage or corn silage and found greater DM intake for the animals that received corn silage (10.5 kg) compared to those that received sugarcane silage (10.2 kg), however, with no differences for average daily gain (1.3 kg/d) between the two silages. …”
Section: Starch Digestion and Corn Processingmentioning
confidence: 97%